2020
DOI: 10.1371/journal.pone.0227823
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus epidermidis in feedings and feces of preterm neonates

Abstract: Staphylococcus epidermidis has emerged as the leading agent causing neonatal late-onset sepsis in preterm neonates; although the severity of the episodes caused by this species is often underestimated, it might exert relevant short-and long-term detrimental effects on neonatal outcomes. In this context, the objective of this study was to characterize a collection of S. epidermidis strains obtained from meconium and feces of preterm infants, and to assess the potential role of the enteral feeding tubes as poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
11
0
Order By: Relevance
“…Interestingly, many of the species positively correlated with metabolites associated with term delivery, including Atopobium vaginae, G. vaginalis, Sneathia sanguinegens, C. aurimucosum, Mobiluncus curtisii, Actinomyces neuii, Ureaplasma urealyticum, Gemella haemolysans, several Prevotella species, Candidatus Lachnocurva vaginae (BVAB1 77 ), BVAB2 and BVAB3 were previously reported to be associated with negative outcomes, such as BV 31,[78][79][80][81] , preterm birth [14][15][16]18,82 and other adverse pregnancy [82][83][84] and neonatal 85 outcomes. We find a similarly paradoxical negative correlation between Staphylococcus epidermidis, previously shown to be associated with BV 86 and late-onset sepsis in preterm neonates 87 , and both tartrate and ethyl glucoside (ρ = -0.28, p = 0.00069; ρ = -0.26, p = 0.0015, respectively; Fig. 3a), which were positively associated with sPTB.…”
Section: A Network Of Microbe-metabolite Associations In Sptbsupporting
confidence: 55%
“…Interestingly, many of the species positively correlated with metabolites associated with term delivery, including Atopobium vaginae, G. vaginalis, Sneathia sanguinegens, C. aurimucosum, Mobiluncus curtisii, Actinomyces neuii, Ureaplasma urealyticum, Gemella haemolysans, several Prevotella species, Candidatus Lachnocurva vaginae (BVAB1 77 ), BVAB2 and BVAB3 were previously reported to be associated with negative outcomes, such as BV 31,[78][79][80][81] , preterm birth [14][15][16]18,82 and other adverse pregnancy [82][83][84] and neonatal 85 outcomes. We find a similarly paradoxical negative correlation between Staphylococcus epidermidis, previously shown to be associated with BV 86 and late-onset sepsis in preterm neonates 87 , and both tartrate and ethyl glucoside (ρ = -0.28, p = 0.00069; ρ = -0.26, p = 0.0015, respectively; Fig. 3a), which were positively associated with sPTB.…”
Section: A Network Of Microbe-metabolite Associations In Sptbsupporting
confidence: 55%
“…Immune modulation by lactic acid bacteria is well-described, the immunomodulatory effect exerted both via induction of IL-10 secretion (de Moreno de Leblanc et al, 2011 ) and silencing of TLR2 signaling (Fischer et al, 2011 ; Kaesler et al, 2016 ). For L. lactis W136 , previous in vitro studies have confirmed that exposure to L. lactis increases IL-10 induction in a suspension of peripheral blood mononuclear cells (Moles et al, 2020 ).…”
Section: Discussionmentioning
confidence: 84%
“…However, the therapeutic potential S. epidermidis was tempered by safety concerns regarding the risks of disease production when applied directly to the delicate nasal and sinus passages. Despite its strong potential as a therapeutic commensal, S. epidermidis can represent a formidable pathogen in certain settings, notably the neonatal intensive care unit and infection of intrvascular foreign bodies (Moles et al, 2020 ) This was thus of particular concern in CRS patients, where anatomical barriers to the sinuses have been removed at surgery, and motivated us to search for a suitable candidate which might retain some of the desirable properties of S. epidermidis , but with lesser safety concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Since S. epidermidis colonizes human skin and mucosa during the first few hours of life, after 24 h, skin of most healthy neonates (84%) is colonized by this bacterial species [ 3 ]. Furthermore, S. epidermidis can cause opportunistic infections in mature and premature neonates.…”
Section: Introductionmentioning
confidence: 99%